Profil Pengobatan Infeksi Saluran Pernapasan Akut (ISPA) Pada Balita Di Puskesmas Rambangaru Tahun 2015 - Yorida Febry Maakh; Ivonne Laning; Rambu Tattu (Research and Community Service Unit, Politeknik Kesehatan Kemenkes Kupang, 2017)
Acute Respiratory Infection (ARI) is an acute disease with a variety of symptoms that often occur in infants. In 2015, ARI was ranked first in the 10 most disease patterns in Rambangaru Health Center with a total of 4350 cases. The purpose of this study was to determine the profile of ARI treatment in infants in Rambangaru Health Center based on age, gender, weight, diagnosis, type of drug, duration of treatment, dosage form, frequency, dose and suitability of the implementation of Integrated Management of Childhood Illness (IMCI). The type of research used is a retrospective descriptive collection of data in the Register and Recipe book, data is recorded, grouped and presented in tables. The results of the study of 366 samples showed that infants aged 1-> 3 years were the most cases with 151 cases (41.25%), male gender 185 cases (50.54%), based on weight 10 kg- <16 kg as many as 258 cases (70.51%), based on the diagnosis is moderate pneumonia ARI 340 cases (90.9%), the type of drug used in ARI rather than pneumonia is 26 cases of ARI (7.10%), in ARI pneumonia while antibiotic Amoxicillin was 263 (71.88%), based on treatment duration was 4 days 306 cases (83.60%), the most widely given dosage forms were pulmonary ARI and Amoxicillin tablets 263 cases (71.88%), the highest frequency is 3 times a day 170 cases (46.44%). Based on the suitability of the implementation of Integrated Management of Childhood Illness (IMCI) on dose, frequency, and duration of treatment 262 cases (78.44%) paracetamol, 263 cases (100%) Amoxicillin tablets, 25 cases (80.64%) Amoxicillin syrup, and 45 Case (97.83%) Cotrimoxazole does not match IMCI.